Bovine poisoning due to Senecio brasiliensis, Lessing, in São Paulo, Brazil - Nazário, Walter; Portugal, Manuel Alberto S. C.; Fancelli, Maria Isabel (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this study was comproved the great mortality of beef cattle for Senecio brasiliensis ingested with forage. The clinical signs; anatomo-pathological study and the alkaloid found in the material coleted, were sufficient for diagnostic of this poisoning.